In vitro and in vivo study on the effects of nutritive media compared with water on the resuscitation of a live attenuated Salmonella Typhimurium vaccine - Siyuan Jia; Andrea R. McWhorter; Samiullah Khan; Daniel M. Andrews; Gregory J. Underwood; Kapil K. Chousalkar (Veterinary Quarterly)
In this study, a commercially available Salmonella Typhimurium vaccine (Vaxsafe ST) reconstituted in either water or nutrient broth, was tested to understand its effects on the in vitro invasion of Caco-2 cells and its transcriptional regulation post-reconstitution. Over time, the invasiveness of Vaxsafe ST was significantly higher following reconstitution in nutrient broth compared with water. Incubation temperature post-reconstitution did not significantly affect the invasion rate. Transcriptome data showed that Vaxsafe ST reconstituted in nutrient broth upregulated genes involved in the two-component system and flagella activity pathways; however, genes involved in host colonization and invasion were unaltered. Genes involved in host colonization and invasion were downregulated after reconstitution in water. Vaxsafe ST reconstituted in a nutritive diluent improved the metabolic activities of the vaccine. The animal experiment demonstrated that vaccine colonization was significantly higher in caeca compared with ileum irrespective of the diluent. Incubating the vaccine in nutrient broth for 30 min before administration did not significantly increase its colonization or organ invasion in chicks. Overall, the findings support the use of nutritive media for the reconstitution of Vaxsafe ST, warranting further investigation to optimize vaccine performance. This study provides a foundation for future work on vaccine reconstitution strategies.